Supplementary Sensorimotor Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The diagnosis, clinical features, video EEG and MRI findings, medical and surgical treatment, pathology, and prognosis in eleven children and adolescents with supplementary sensorimotor area seizures (SSMA) are reported from the Departments of Neurology, Neurosurgery, and Radiology, Cleveland Clinic Foundation, Cleveland, Ohio.